Walka stronnictw o tron biskupi w Rzymie w drugiej połowie IV wieku, czyli od papieża św. Juliusza przez Liberiusza do św. Damazego - Spychała, Dariusz (Studia Europaea Gnesnensia, 2012)
In the 4th century AD, with the ongoing Christological debate, personal ambitions, political, ideological and economic problems came to the surface, which ravaged the structure of the Universal Church. The east of the Empire was a particularly susceptible area, but similar phenomena were also taking place in the Eternal City. In the latter half of the 4th century, against the backdrop of debate sparked by the teachings of Arius and the intervention of Constantius II in the internal matters of the Roman Church, divisions ensued. The causes behind such state of affairs appear so complex that one cannot conclusively state whether this resulted from personal ambitions or whether the issue of maintaining orthodoxy was at its roots. It seems that in the discussed events the Aryan affair was merely a pretext for pursuing now indeterminable goals of the groups into which the community of Roman Christians had been split.